Cancer during pregnancy: Factors associated with termination of pregnancy and perinatal outcomes. (June 2021) - Barrois, Mathilde; Anselem, Olivia; Pierga, Jean Yves; Goldwasser, François; Bouscary, Didier; Alessandrini, Vivien; Goffinet, François; Tsatsaris, Vassilis
Abstract: Background: Cancer during pregnancy is rare (about 1/1000 pregnancies) and its diagnosis raises the question of whether or not to continue the pregnancy. Objectives: The primary objective of our study was to evaluate associated factors with termination of pregnancy in cases of cancer during pregnancy. Secondary objectives were to evaluate maternal and neonatal outcomes when pregnancy is continued. Study design: We conducted a retrospective, single-center study between January 2009 and December 2019 including 2 groups of patients those who underwent termination of pregnancy and those who continued pregnancy. Patients were distributed in 3 categories breast cancer, blood cancer and other cancers. Results: A total of 71 pregnancies associated with cancer were included. Twenty patients (28.16 %) underwent termination of pregnancy. The median gestational age at diagnosis was significantly earlier in the termination of pregnancy group compared with the ongoing pregnancy group (9 vs 22 weeks, p < 0.01). Blood cancer was more frequent in the termination group 7 (35 %) compared to continuous pregnancy 8 (15.7 %) as other cancers 8 (40 %) in the termination group vs 5 (9, 8 %). Conversely breast cancer what was less frequent in the termination group 5 (25 %) vs 38 (74, 5 %) (p < 0.01). In the continued pregnancy group, there was a high rate of induced prematurity (35.5 %) and scheduled delivery to optimize maternal oncologic management (78.4 %). Conclusion: The rate of termination of pregnancy remains high particularly in case of non-breast cancer and early pregnancy detection. Scheduled preterm birth is frequent when pregnancy is continued in order to optimize of cancer management.